2013
DOI: 10.1007/s00464-013-3014-4
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus laparoscopic coloanal anastomosis with or without intersphincteric resection for rectal cancer

Abstract: Robotic surgery is increasingly used in the field of rectal cancer surgery. This study aimed to compare the short- and long-term outcomes between robotic and laparoscopic ultralow anterior resection (uLAR) and coloanal anastomosis (CAA). Between January 2007 and December 2010, a retrospective chart review was performed for all patients with low rectal cancer who underwent curative uLAR and CAA with or without intersphincteric resection using either a robotic or a laparoscopic approach. The study excluded patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 23 publications
3
105
0
Order By: Relevance
“…The final analysis included five studies with a total n of 685 patients; of these, 317 patients underwent hybrid robotic resection and 368 underwent laparoscopic resection [8,[15][16][17][18]. Patient demographics and perioperative variables are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final analysis included five studies with a total n of 685 patients; of these, 317 patients underwent hybrid robotic resection and 368 underwent laparoscopic resection [8,[15][16][17][18]. Patient demographics and perioperative variables are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…It remains yet to be demonstrated that the benefits offered by the robot outweigh the additional costs incurred by its use [9,16,19].…”
Section: Discussionmentioning
confidence: 99%
“…We previously in vivo 32: 611-623 (2018) 616 Figure 2. Continued conducted a meta-analysis, by 12 randomized controlled trials, to evaluate and compare the short-and long-term outcomes of LAS and OS for the treatment of patients with rectal cancer (16). The operative time for OS was significantly shorter, by 40.96 min, than that for LAS.…”
Section: Discussionmentioning
confidence: 99%
“…Then the remaining 42 articles were subjected to full-text examination and the following studies were further eliminated, including 24 articles without longterm oncologic outcomes, seven studies irrelevant to the comparison of DVSS versus LS/open surgery, and one plan. Finally, 10 eligible articles 5,11,[13][14][15][21][22][23][24][25] were included in the present meta-analysis.…”
Section: Eligible Studiesmentioning
confidence: 99%